Healers and midwives: knowledge that challenge - Manrique García, Diana. (Instituto de Filosofia e Ciencias Humanas-UFRGS, 2022)
This text addresses some care and healing practices of the Itonama community in the Bolivian Amazon, where women occupy a leading place. Practices crossed by a collective ethic of care that emerge as a political place of dispute, decision and incidence, while claiming an ancestral episteme, stress the modern ontology, favoring from their place of healers and midwives the reinvention of feminine subjectivities and the vindication of the bond in communal relations. The work is based on empirical data derived from field work in the framework of the author’s research and doctoral thesis.
Curanderas y parteras: saberes que reivindican y tensionan
Keywords: Bolivian Amazon; Cares - Tensions; Sanadores; Matronas